CD45+ erythroid progenitor cells as potential biomarkers for disease progression in hepatitis B virus-related acute-on-chronic liver failure - Nan Zhang; Hai-Shi Wu; Xiu-Qing Pang; Cheng-You Yu; Xing Li; Zhi-Liang Gao (BMC Gastroenterology)
Abstract Background Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is characterized by immune dysregulation and systemic inflammation, which lead to high mortality. Although immunosuppressive CD45+ erythroid progenitor cells (EPCs) percentages are elevated in chronic hepatitis B (CHB) and are associated with disease progression, their role in HBV-ACLF remains unclear. This study aims to evaluate the impact of CD45+ EPCs on disease progression in patients with HBV-ACLF. Methods In this retrospective study, we analyzed the data of 102 patients with CHB and 65 patients with HBV-ACLF receiving standard drugs treatment from the Third Affiliated Hospital of Sun Yat-sen University between January 2021 and December 2023. HBV-ACLF diagnosis followed the Chinese Group on the Study of Severe Hepatitis B–Acute-on-Chronic Liver Failure criteria, with strict exclusion of comorbidities. Peripheral blood mononuclear cells (PBMCs) were isolated via density gradient centrifugation, and CD45+ EPCs (CD45+ CD71+ CD235a+) were quantified using flow cytometry. Liver tissue EPCs were assessed by immunofluorescence in biopsy/transplant specimens. Receiver operating characteristic (ROC) and multivariable logistic regression analyses identified prognostic factors associated with disease progression. Results Our findings revealed that patients with HBV-ACLF had significantly elevated percentages of CD45+ EPCs compared with those with CHB. We also observed strong correlations between CD45+ EPC percentages and creatinine concentration, leukocyte count, and neutrophil-to-lymphocyte ratio (NLR). The area under the ROC curve for CD45+ EPCs was 0.718, indicating a significant predictive value [95% confidence interval (CI): 0.586–0.851, p = 0.004]. High CD45+ EPC percentage was associated with a greater incidence of hepatic encephalopathy (30.8% vs. 10.3%, p = 0.037) and higher rates of disease progression (73.1% vs. 35.9%, p = 0.003). Multivariate logistic regression analysis identified international normalized ratio (INR) and NLR as independent predictors of poor 28-day outcomes (INR odds ratio [OR] = 6.098, p < 0.001; NLR OR = 1.354, p = 0.005). Conclusions The percentage of CD45+ EPCs in PBMCs may be a potential biomarker for predicting 28-day disease progression in patients with HBV-ACLF. These findings highlight their possible clinical utility for risk stratification.